Machinery's handbook - Oberg, Erik , 1881-; Horton, Holbrook Lynedon , 1907-; Jones, Franklin D. , 1879-1967; McCauley, Christopher J.; Ryffel, Henry H. (Industrial Press, Inc., 2020)
"Machinery's Handbook has served as the principle reference work for in metalworking, design, and manufacturing facilities, and in technical schools and colleges throughout the world, for nearly 100 years. It is a comprehensive and practical tool, combining the most basic and essential aspects of sophisticated manufacturing practice"-- Provided by publisher